Marriage as a Form of Domestic Violence in the Pakistani Bride by Bapsi Sidhwa: Unveiling the Hidden Dimensions of Domestic Violence in Pakistani Marriages (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of the present paper is to demonstrate the multiple dimensions of domestic violence against women to control the lives of women to dominate in the society especially in patriachal society which are presented in The Pakistan Bride by Bapsi Sidhwa, a Pakistani novelist. Domestic violence has always been a long standing constraint in the progress and prosperity of women for a long time. Being an acknowledged novelist, Sidhwa endeavours to demonstrate all the aspects of violence in the marriage to bring the hidden negative effects of marriage on women’s lives on the surface. Having practical experience of problems faced by women in patriarchal society, she refutes the sacred notion of marriage in which women are entrapped through different social codes drafted by male representatives of society. An attempt has been made in this paper to present all the social codes and tools used by men to control women through the so-called sacred institution of marriage for centuries.